Evaluation of the effects of Astragalus polysaccharides as immunostimulants on the immune response of crucian carp and against SVCV in vitro and in vivo - Liu, Jia; Zhang, Peijun; Wang, Bo; Lu, Yuting; Li, Liang; Li, Yuehong; Liu, Shaojun (Comparative biochemistry and physiology. Toxicology & pharmacology, 2022)
This experiment was conducted to evaluate the immunomodulatory effect and antiviral activity of Astragalus polysaccharides (APS) in crucian carp and epithelioma papulosum cyprinid (EPC) cells. Two diets containing 0 and 2 g/kg, APS were fed crucian carp for 56 days. The results showed that supplementation with APS significantly upregulated the immune-related indices including the levels of IgM, the activities of LZM, AKP and ACP, and the contents of C3 and C4. At the same time, compared with the CK group, adding APS to the feed significantly upregulated the expression of IL-8, IL-10, IL-1β, IFN-α, IFN-γ, MyD88, TGF-β and TNF-α in the spleen, kidney, liver and intestine of crucian carp. In addition, when the crucian carp were injected with SVCV, the survival rates of fish in the APS group and the control group were 48.87% and 13.76%, respectively. These results indicated that dietary APS could improve the resistance of crucian carp against SVCV infection. APS also significantly decreased viral titer and inhibited apoptosis induced by SVCV in EPC cells. These results indicated that APS could stimulate the immune response of crucian carp and improve the abilities of crucian carp and EPC cells to resist SVCV infection. •Supplementing Astragalus polysaccharides can significantly up-regulate immune parameters and enhance the immune response of crucian carp.•Dietary Astragalus polysaccharides could improve the resistance of crucian carp against SVCV infection.•Astragalus polysaccharides could significantly decrease viral titer and inhibited apoptosis induced by SVCV in EPC cells.